PENINGKATAN KEMAMPUAN MENULIS DESKRIPSI DENGAN STRATEGI MODELLING - Iskandar Iskandar (IAIN Palopo, 2018)
This study aims to improve the ability to write descriptions for fifth-grade students of SD Inpres Pabbangiang Gowa Regency which includes the content of ideas, content organization, grammar, diction, and spelling. This research is a classroom action research conducted in two cycles. The research subjects were students of class V in Pabbangiang Inpres Elementary School, Gowa Regency, totaling 43 students. Data collection techniques used are observation, interviews, and tests. The entire data obtained is analyzed through stages: data identification, data reduction, data presentation, and conclusions. The results showed that the results of the pre-action test in the description writing skills of fifth-grade students of Pabbangiang Inpres Elementary School in Gowa Regency which included aspects of the content of ideas, content organization, grammar, diction, and spelling were still lacking. After an action is taken through cycles I and II by applying the semantic mapping strategy in learning to write descriptions, the students' skills increase from the category of being very good. The final results of this study indicate that the application of modeling strategies can improve students' writing skills which include aspects of content ideas, content organization, grammar, diction, and spelling.